The crisis, an opportunity to accelerate change - Gamio Aita, Pedro (2020)
In this article we examine the current situation of our country regarding the Pandemic and the excessive use of pollutant energy (mainly based in hydrocarbons), as well as the requirement of a gradual change to cleaner and renewable energy which will allow us to face the climate change. Also, the need of public politics to promote the sustainable and healthy development of our country.